Why do tumor-infiltrating lymphocytes have variable efficacy in the treatment of solid tumors? - Li, Biaoru (Frontiers in Immunology, 2022)
Lymphocytes in tumor tissue are called tumor-infiltrating lymphocytes (TILs), which play a key role in the control and treatment of tumor diseases. Since the discovery in 1987 that tumor-infiltrating lymphocytes (TILs) cultured can kill tumor cells more than 100 times compared with T cells cultured from peripheral blood for melanoma, it has been confirmed that cultured TILs can successfully cure clinical patients with melanoma. Since 1989 after we investigated TIL isolation performance from solid tumors, we modified some procedures to increase effects, and thus, successfully established the new TIL isolation and culture methods in 1994. Moreover, our laboratory and clinicians who used our cultured TIL have published more than thirty papers. In order to improve the efficacy of TIL, we further study TIL efficacy to treat solid tumor disease about thirty years. Here, the three questions of TIL have been mainly studied since then. Those are: "How do TILs remain silent in solid tumor tissue?" "How do TILs attack homologous and heterologous antigens from tumor cells of solid tumor?" "How do TILs infiltrate solid tumor tissue from a distance into tumor sites to kill tumor cells?" With the researches on these three issues, these questions are now more and more solved. In the review, I will summarize the main issues for TIL to treat solid tumors. This review aims to study the killing function of TILs from solid tumor tissues, thereby ultimately introducing the optimal strategy for the patients suffering from solid tumors by personalized immunotherapy in the near future.